Seguranca do trabalho no canteiro de obras: uma reflexão para o arquiteto - Castro, Cecília Maria de (1995)
This thesis intends to make the acbitect awae of the safty conditions of the constction work. The high accident rate, material waste and man-power, high cost and improvisation highlighit the gap refring to safety and health prevention, which have to be part of the project. Highlights the architect needs to facilitate the constrctionof his / her project, based on a quality control and safty models that, nowadays, conside the worker one of the most important elements in a successful constructing process. The tone of this work expresses that the humanism that accompanies the entire formation of the Architect, at the time of production excludes the isolated man of this process, needing to be revised. Historical, legal, technical and ciltual arguments, besides the concept of constuctibility, are used in thiss thesis in order to make sure that the achitect's absence fom the construction process aﬀects quality.